Delivering Covid‐19 research during the UK pandemic: Experiences of a local research taskforce. (26th November 2021) - Gardiner, Siobhan; MacLellan, Jennifer
Abstract: Aim: During the COVID‐19 pandemic in the UK, clinical research nurses had to work in new ways and under significant pressure to generate evidence for the developing health crisis. Research nurse support needs, personal and professional challenges have not been explored. This study addresses that gap, generating learning for continued support and development of the research nurse specialty and its ability to respond to public health priorities. Design: We employed a qualitative exploratory approach through online open‐ended interviews to explore research nurses' experiences of delivering research during the pandemic using principles of Grounded Theory. Methods: Fifteen research nurses in the local research taskforce were identified through purposive sampling. Qualitative interviews were conducted online between November 2020 and January 2021 and analysed using the principles of constructivist grounded theory. Results: Three themes of adapting to uncertainty, inclusive leadership and finding validity in the stretch zone were generated in the analysis. Conclusion: A model of inclusive leadership and support can facilitate high‐functioning performance in a research team, supporting a rapid, confident and efficient response to research needs. Impact: Research nurses, a previously invisible workforce, have proved critical to the pandemic response. This study explores the experiences of a team of redeployed research nurses and develops a theory of their experience as they were undertaking the rapid delivery of urgent public health studies during COVID‐19. What was found was a process of adaptation and resilience through collaborative teamwork, a strong sense of purpose and role validation enabled by an inclusive leadership style. This work will drive future development of a model of research nursing with a focus on collaboration between research and clinical colleagues.